La agresividad infantil en el proceso aúlico de los niños de primero de básica de la escuela Isidro Ayora. - Toapanta Núñez, Mercy Ángela (2021)
The current investigation against the proposed problem allowed to analyze the aggressiveness in the classroom process in the boys and girls of the first year of the basic education school "Isidro Ayora," to provide specific solutions in order to accomplish with the proposed purpose; The investigative purpose of this work was to promote peaceful school environments and reduce aggressiveness problems in the classrooms through workshops with a series of strategies based on the development of emotions, facilitating children to modify behavior and improving knowledge in the learning process. A quantitative and quality methodology was applied with evaluation techniques and instruments for data collection, through activities applied in an appropriate way in learning, thus, data was obtained in a structural way, resulting in the reduction of aggressive behaviors of boys and girls in the classroom, because in the Pre-test there was 38% of aggressive behaviors in the boys and girls, and in the post-test it dropped to 2%, thus achieving, an effective proposal applying workshops positive strategies, peaceful school environments, calm activities through emotions with educational content that has allowed them to improve their rules of coexistence, behavior and controlling their emotions.